(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
This research evaluated the role of the ESL teacher and the use of modern techniques on teaching deletion. Questionnaire and oral interview were the instruments that the researcher used to collect the data. The research findings showed that most of the students do not know how to pronounce some words correctly, that is, they have a problem with the silent words that have silent letters. The findings also revealed that some teachers do not pronounce the words correctly. It is concluded that the teachers transfer their inadequacy to the students and do not use appropriate techniques in teaching pronunciation especially words with silent letters. The researcher recommends that only teachers who are B.A. and B.A.Ed English graduates should teach the subject and they too, must use appropriate techniques when teaching pronunciation especially words with silent letters/sounds